(untitled) (Journal of Comparative & International Higher Education, 2022)
University ranking is a buzzword that attracts both national and global attention. At the very outset, the book’s central theme revolves around this buzzword. Through a critical lens, the book analyses the Big Three ranking systems and fine points of the methodology adopted, the weighing of the different indicators, and the recent amendments.